Ancient Kedah : a Srivijayan Mandala in the Malay Peninsula - Muhammad Nu’man Mohd Nasir; Zuliskandar Ramli (Ikatan Ahli Arkeologi Malaysia, Universiti Kebangsaan Malaysia, 2022)
Ancient Kedah was a polity located in the Malay Peninsula that have been closely integrated into the Srivijaya ring of mandala. Based on various foreign records that were made by the Indians, Chinese and Arabs have stated that Ancient Kedah was under the influence of the polity known as Srivijaya. This study aims to discuss the relationships that exist between these two polities that have shaped the history of the Malay Peninsula and Insular Southeast Asia. Written records concerning the existence of Ancient Kedah, its relation with Srivijaya and also previous archaeological studies in Kedah have been studied to tackle this topic. Ancient Kedah and Srivijaya indeed have a close relationship which, as the former is a mandala of the latter. However, as a mandala, Ancient Kedah still retain its autonomous power to govern its polity. Through the Srivijaya sociopolitics, we can have a better understanding on some aspects of Ancient Kedah sociopolitical structure as the latter does not have any written records concerning this matter. Ancient Kedah position as a strategic port-city with lucrative economic opportunities and the religious factor, caused this polity to be closely integrated into the Srivijaya rings of mandala.